2023
DOI: 10.1002/adfm.202302542
|View full text |Cite
|
Sign up to set email alerts
|

Solution‐Mediated Hybrid FAPbI3 Perovskite Quantum Dots for Over 15% Efficient Solar Cell

Abstract: Organic–inorganic formamidinium lead triiodide (FAPbI3) hybrid perovskite quantum dot (QD) is of great interest to photovoltaic (PV) community due to its narrow band gap, higher ambient stability, and long carrier lifetime. However, the surface ligand management of FAPbI3 QD is still a key hurdle that impedes the design of high‐efficiency solar cells. Herein, this study first develops a solution‐mediated ligand exchange (SMLE) for preparing FAPbI3 QD film with enhanced electronic coupling. By dissolving optima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…In addition, Li et al reported a methylammonium iodide (MAI)-assisted solution-mediated ligand exchange (SMLE) method to adjust the surface and internal chemical environment of FAPbI 3 PQDs in solution to form mixed-cation PQDs partially doped with MA cations. [55] The MAI-SMLE treatment has a negligible effect on the crystal structure of FAPbI 3 PQDs but can effectively reduce the density of surface ligands and passivate the trap states. Based on the aforementioned, the SMLE FAPbI 3 PQDSC obtained a champion PCE of 15.10%, which resulted from the significant improvement in the short-circuit current density ( J SC ) and fill factor (FF), which is much higher than that of the control device (12.12%).…”
Section: Pqd Solar Cellsmentioning
confidence: 99%
“…In addition, Li et al reported a methylammonium iodide (MAI)-assisted solution-mediated ligand exchange (SMLE) method to adjust the surface and internal chemical environment of FAPbI 3 PQDs in solution to form mixed-cation PQDs partially doped with MA cations. [55] The MAI-SMLE treatment has a negligible effect on the crystal structure of FAPbI 3 PQDs but can effectively reduce the density of surface ligands and passivate the trap states. Based on the aforementioned, the SMLE FAPbI 3 PQDSC obtained a champion PCE of 15.10%, which resulted from the significant improvement in the short-circuit current density ( J SC ) and fill factor (FF), which is much higher than that of the control device (12.12%).…”
Section: Pqd Solar Cellsmentioning
confidence: 99%
“…After that, Wang et al introduced protonated oleylamine (OAm) in situ to strengthen the ligand binding at the surface of FAPbI 3 PQDs, and their PCE was enhanced to 13.80% . Subsequently, the PCE and stability of FAPbI 3 PQDSCs have been developed through the surface ligand regulation, the component dopant of QDs, and the structure optimization of the device. So far, the highest efficiency of FAPbI 3 PQDSCs reported is 15.10% . Although substantive progress has been obtained in the efficiency of PQDSCs, the reaction mechanism between the surface of the QD and the functional ligand has not been resolved and understood thoroughly. ,, …”
Section: Introductionmentioning
confidence: 99%
“…As is widely known, superfluous oleic acid (OA) and OAm ligands are anchored on the surface of FAPbI 3 PQDs prepared by the hot injection method, leading to poor performance. , Meanwhile, due to the weak binding energy between insulating long-chain ligands and QDs, it tends to lose surface ligands during the process of QD purification and solid film post-treatment, which resulted in the aggregation or even degradation of QDs. , Compared with a FAPbI 3 bulk thin film, surface defects and more grain boundaries are serious obstacles to carrier extraction and transport in the FAPbI 3 PQD solid film toward the relatively lower current density for their solar cells . In addition, QD arrays with undesired uniformity may be attributed to the existence of overmuch capping insulating ligands to form disordered energy distribution .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[14][15][16][17][18][19][20] Therefore, much effort has been dedicated to passivate the surface of CsPbX 3 NCs by introducing various kinds of ligands with enhanced bonding energy, such as trioctylphosphine (TOP), 21 2,2 ′ -iminodibenzoic acid (IDA), 22 glutathione, 23 4-bromo-butyric acid, 24 etc. [25][26][27][28][29][30][31][32] Our previous report suggested that short-chain ligands (such as octanoic acid and octylamine) possess larger polarity in comparison to the commonly used oleylamine (OLA) and oleic acid (OA). The increased polarity leads to stronger adsorption energy, which can result in improved structural stability of CsPbX 3 NCs.…”
Section: Introductionmentioning
confidence: 99%